The Relationship Between Spiritual Well-Being And Stress Levels In The Elderly - Arini, Intan; Zulfitri, Reni; Agrina, Agrina (Institute Of Computer Science (IOCS), 2025)
Elderly is characterized by a variety of changes and issues, such as issues with the biological, psychological, and social facets of life. Elderly may experience stress due to the numerous changes and issues that arise. One way to overcome the stress is by fulfilling the well-being of spirituality. Methods: The research is a quantitative study using a descriptive correlational design and a cross-sectional approach. The research sample consisted of 92 elderly individuals with inclusion criteria of being ? 60 years old and Muslim, using purposive sampling technique in Kubang Jaya Village. Data were analyzed using the chi-square statistical test. Result: It was found that the majority of the elderly have high spiritual well-being with a normal stress level of 41 (44.6%) elderly. The results of the chi-square test indicate a significant relationship between spiritual well-being and stress levels in the elderly, with a p-value of 0.004. Conclusion: The higher the spiritual well-being, the lower the stress levels in the elderly.